KADAR PROSTAGLANDIN DAN ENDORFIN PADA REMAJA DISMENORE PRIMER YANG DIBERI SENAM DISMENORE DAN ABDOMINAL STRETCHING EXERCISE - Nur Partiwi; Arsyad Aryadi; Nilawati Andi (Poltekkes Kemenkes Bandung, 2020)
This study aims to determine the levels of prostaglandins and endorphins in adolescents with primary dysmenorrhea who are given dysmenorrhea and abdominal stretching exercise. The study was a quasi-experimental study with a post-test only control group design carried out in Islamic Boarding Schools with a sample of 36 primary dysmenorrhea adolescents divided into 3 groups: 12 respondents doing gymnastics dysmenorrhea, 12 respondents doing abdominal stretching exercises and 12 respondents doing nothing (Control). Dysmenorrhea exercises and abdominal stretching exercises are carried out for 4 consecutive days in the afternoon before the first day of menstruation. Furthermore, blood is drawn on the first day of menstruation for the examination of levels of prostaglandins and endorphins using the Enzyme-linked immunosorbent assay (ELISA) Kit. After intervening, prostaglandin levels in the abdominal stretching exercise group (345 pg/ml) were lower than those not given the intervention (360 pg/ml) while the gymnastics dysmenorrhea group experienced an increase in prostaglandin (391 pg/ml) compared to the control but there was no significant difference statistically. However, endorphins in the intervention group of gymnastics dysmenorrhea (138 pg/ml) and abdominal stretching exercise (115 pg/ml) were higher than those in the intervention group (112 pg/ml) although statistically showed no significant difference. The results of this study indicate gymnastics dysmenorrhea can stimulate endorphin secretion but not accompanied by a decrease in prostaglandin levels. Different things found in abdominal stretching exercises have been shown to increase endorphins followed by decreased prostaglandin levels. This shows that abdominal stretching exercise is more effectively used as a nonpharmacological therapy type of physical exercise in primary dysmenorrhea. Keywords : Prostaglandins, Endorphins, Gymnastics Dysmenorrhea, Abdominal Stretching Exercise